2001
DOI: 10.1002/1097-0142(20010215)91:4<869::aid-cncr1075>3.3.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Equal care ensures equal survival for African‐American women with cervical carcinoma

Abstract: BACKGOUND.It was the purpose of this study to investigate whether race is an independent prognostic factor in the survival of patients with cervical carcinoma in a health care system with minimal racial bias, and few barriers to access to care. METHODS. RESULTS.One thousand five hundred fifty-three patients were obtained for review.Sixty-five percent of patients were Caucasian, and 35% were minorities. Of the minorities, 29% were African Americans (AAs). Mean age of diagnosis was similar among AAs and Caucasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 12 publications
2
29
0
Order By: Relevance
“…One study reported that when African-American women received the same level of care for cervical cancer as did their white counterparts, they had similar 5-year survival rates. 38 This finding suggests that inequality in care may play a substantial role in the observed inequality in survival rates for patients with anal cancer, assuming that the relation between treatment and survival is similar for patients with cervical cancer and patients with anal cancer. Furthermore, a recent study reported that patients with anal cancer who were HIV positive were more likely to have treatment-related toxicity and may have been more likely to die of malignant disease after treatment.…”
Section: Discussionmentioning
confidence: 94%
“…One study reported that when African-American women received the same level of care for cervical cancer as did their white counterparts, they had similar 5-year survival rates. 38 This finding suggests that inequality in care may play a substantial role in the observed inequality in survival rates for patients with anal cancer, assuming that the relation between treatment and survival is similar for patients with cervical cancer and patients with anal cancer. Furthermore, a recent study reported that patients with anal cancer who were HIV positive were more likely to have treatment-related toxicity and may have been more likely to die of malignant disease after treatment.…”
Section: Discussionmentioning
confidence: 94%
“…In cancer populations where treatment has been equalized, differences in cause-specific survival between social or racial groups are small or nonexistent. [42][43][44][45][46] However, whether patterns of treatment can explain the international survival differences for breast cancer has yet to be examined.…”
Section: Possible Causal Explanationsmentioning
confidence: 99%
“…6,7,14,[16][17][18][19][20][21][22][23] Unlike information on stage and treatment, however, databases used by public health researchers generally do not include information on individual SES. SES has been described in the cervical cancer literature using various combinations of measures, including poverty level, occupation, educational level, and insurance status.…”
mentioning
confidence: 99%